Palladium-catalyzed desulfurative Sonogashira cross-coupling reaction of 3-cyano assisted thioamide-type quinolone derivatives with alkynes1. Issue 60 (2nd July 2015) - Wu, You; Xing, Yongning; Wang, Jie; Sun, Qi; Kong, Weiqi; Suzenet, Franck
<x xml:space="preserve">Abstract</x> A Pd-catalyzed Cu-mediated desulfurative Sonogashira cross-coupling reaction of thioamide-type quinolone derivatives was proposed for the construction of Csp2–Csp bonds.